Stressful sleep. Issue 2 (February 2016) - Jun, Jonathan C.; Polotsky, Vsevolod Y.
Few would challenge the assertion that the inability to breathe is stressful. In fact, inhaling carbon dioxide to simulate asphyxia is a time-honoured research protocol to unmask panic disorder [1]. Sleep loss is also stressful, as evidenced by increased cortisol and sympathetic tone in insomnia [2] or sleep deprivation [3, 4]. In the case of obstructive sleep apnoea (OSA), impaired breathing efforts may jolt the sleeper awake with surges in heart rate, blood pressure, sympathetic nerve activity and catecholamines. The treatment of OSA normalises many of these parameters [5]. Hence, OSA clearly engages the "fight or flight" response; a term coined in 1915 by Walter Cannon to describe activation of the sympathetic nervous system to defend homeostasis [6]. In 1936, Hans Selye defined stress as "the non-specific response of the body to any demand upon it" and postulated the General Adaptation Syndrome [7] describing how repeated physical or psychological demands elicit initially adaptive, then maladaptive responses. When stress induces negative consequences, it shifts from potentially productive stress (eustress) to damaging distress. Unrelenting distress may lead to a variety of disorders through hypercortisolism [8]. The ideas of Cannon and Selye have helped formulate the still widespread view that all threats, whether real or imagined, are countered by a global and stereotyped activation of the neuroendocrine system. Obstructive sleep apnoea increases the stress hormone cortisol, and CPAP can correct this problem http://ow.ly/Wdy5F